Analisis Pengaturan Pelindungan Pekerja Migran Indonesia (PMI) Perempuan Ilegal Korban Image-Based Sexual Abuse: Telaah Perspektif HAM dan Intersectionality Theory - Dimas Saputra (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) women are a group that is vulnerable to violence including non-physical sexual violence based on images. Ideally, the state should be present as an effort to protect this vulnerable group, but unfortunately this is not the case for those with illegal status, with the argument that the government's legality principle seems to turn a blind eye to it. However, this raises a big question regarding how legal protection actually is and should be. This study uses a juridical-normative research method with a regulatory-legislation approach, a conceptual approach and a comparative approach. The data used are secondary data with primary and secondary legal materials. The results of the study show that there is a disparity in legal protection between legal and illegal workers, the PPMI Law specifically only guarantees legal protection for PMI law. In fact, from a human rights perspective, the right to dignity agrees on the protection of illegal female PMI not only as workers but also as responsible human beings. Both implicitly and specifically, Article 28D paragraph (1) and Article 28G of the 1945 Constitution of the Republic of Indonesia and international commitments through the ICRMW have actually guaranteed the protection of every individual as a human being, including illegal female migrant workers, but the PPMI Law as lex specialis has not heeded it. Through the Intersectionality Theory, it was also found that there are multiple vulnerabilities, structural discrimination, and policies that are not sensitive to gender, this makes the conditions of illegal female migrant workers even more ironic.